Analisis Pemberian Kredit Terhadap Rentabilitas Pada Sektor Keuangan Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2014-2018 - Tri Amalia Sukarno (Exchall: Economic Challenge, 2021)
This study aims to examine and provide empirical evidence regarding the analysis of credit granting towards profitability in the Banking Sub-Sector Companies. The independent variable used in this study is the provision of credit and the dependent variable used in this study is profitability. The hypothesis proposed is "There is a positive relationship between lending and profitability". In the study using a sample of 25 samples, with details of 5 companies with research for 5 years (2014 - 2018) from the report of each Banking Sub Sector Company. The research data obtained from the financial statements of each Banking Sub Sector Company are then processed by researchers and analyzed using analytical test equipment. The results of the study using the correlation coefficient is 0.725 which means that the relationship is strong or that there is a relationship between lending and profitability. The results of the t-test were significant at 5.07, so it was stated that the t-test was 5.044, greater than 2.068 or fell in the rejection area of ​​H0. The coefficient of determination is 0.4744 which implies that rentability is affected by the provision of credit by 47.44% while rentability is influenced by other factors giving credit reaching 52.56%. Simple linear regression is used as a statistical method. With the linear regression equation Y = 1.418 + 0.004 X then the meaning is that if the value of X is increased by one unit then Y will increase by 0.004 on the constant 1.418.